2023
DOI: 10.3390/antibiotics12061072
|View full text |Cite
|
Sign up to set email alerts
|

Use of Newer and Repurposed Antibiotics against Gram-Negative Bacteria in Neonates

Abstract: Antimicrobial resistance has become a significant public health problem globally with multidrug resistant Gram negative (MDR-GN) bacteria being the main representatives. The emergence of these pathogens in neonatal settings threatens the well-being of the vulnerable neonatal population given the dearth of safe and effective therapeutic options. Evidence from studies mainly in adults is now available for several novel antimicrobial compounds, such as new β-lactam/β-lactamase inhibitors (e.g., ceftazidime–avibac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…A drug that could play a key role in MDR Gram-negative infections is Colistin, a molecule with extremely effective action against this class of bacteria, which was previously excluded due to collateral nephrotoxicity [ 59 ]. Ambreen et al demonstrated positive effects of Colistin in a neonatal population of MDR sepsis in Pakistan with a moderate frequency of related adverse effects (nephrotoxicity: 5.2%; seizures: 13.7%; electrolyte imbalance: 18.3%) [ 61 ].…”
Section: Early-onset Sepsismentioning
confidence: 99%
“…A drug that could play a key role in MDR Gram-negative infections is Colistin, a molecule with extremely effective action against this class of bacteria, which was previously excluded due to collateral nephrotoxicity [ 59 ]. Ambreen et al demonstrated positive effects of Colistin in a neonatal population of MDR sepsis in Pakistan with a moderate frequency of related adverse effects (nephrotoxicity: 5.2%; seizures: 13.7%; electrolyte imbalance: 18.3%) [ 61 ].…”
Section: Early-onset Sepsismentioning
confidence: 99%
“…The first category comprises various antibiotics that have been modified to overcome antimicrobial resistance. The second category includes a few older antibiotics used in the past for different purposes [24]. Many newer antibiotics include a combination of β-lactam + βlactamase inhibitor, but the microorganisms responsible for neonatal sepsis are resistant to most of these.…”
Section: Older Antibioticsmentioning
confidence: 99%
“…The first category comprises various antibiotics that have been modified to overcome antimicrobial resistance. The second category includes a few older antibiotics used in the past for different purposes [26]. Many newer antibiotics include a combination of β-lactam + β-lactamase inhibitor, but in most of these, the microorganisms responsible for neonatal sepsis are resistant.…”
Section: Older Antibioticsmentioning
confidence: 99%